PEMBERDAYAAN PEREMPUAN MELALUI KWT UNTUK MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT DESA SUKANEGARA - Dewi Iskandar; Nandang Faturohman; Ahmad Fauzi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Because they can be used as a resource, farmer women's groups in rural areas can become a place of hope for farming families. In Sukanegara Village, This study's objectives are to: Gunungkencana District, Lebak Regency, Banten Province (1) the stages of women's empowerment through successful women farming group activities; (2) women's participation in empowerment through successful women's farmer group activities; and (3) the welfare of the economic community after participating in women's empowerment through successful women's farmer groups. A qualitative approach using descriptive method is the strategy applied. Interviews, observations, and documentation are the methods and rules for collecting data. Three additional strategies are used in addition to the data analysis methodology in this study: data reduction, data display, and finally conclusion and verification. Ten people provided data for this study, including two team members and eight women farmers. The research's findings lead to the following conclusions: the stages of empowerment are carried out quite well, with each stage being followed alternately; women's participation is involved and said to be active in empowering women through successful farmer women's groups; and in the field of community economic welfare, members of successful women farmer groups are able to be independent so as to be able to meet their financial needs.